The Effect of Alexithymia on Attentional Bias Toward Emotional Stimuli in Depression: An Eye-Tracking Study - Bergman, M. Annemiek; Vissers, Constance Th. W. M.; Collard, Rose M.; van Eijndhoven, Philip; Schene, Aart H.; Vrijsen, Janna N. (Frontiers in Psychiatry, 2021)
Alexithymia – reflecting deficits in cognitive emotion processing - is highly prevalent in individuals with depressive disorders. Subsequently, mixed evidence for attentional bias is found in these individuals. Alexithymia may be a potential influencing factor for attentional bias in depression. In the current study 83 currently depressed (CD) and 76 never depressed controls (ND) completed an eye-tracker task consisting of valenced (non-)social pictures. Alexithymia scores were also included as a moderator, both as a continuous measure and categorical (so high versus low alexithymia). No group difference or moderating effect of alexithymia was found on attentional bias. Thus, alexithymic symptoms, included both dimensionally as categorically, may not influence biased attentional processing in depression compared to never depressed individuals. Thus, it is important to explore potential other explaining factors for the equivocal results of biased attentional processing of emotional information in depression found